Self-aligned mechanical attachment of carbon nanotubes to silicon dioxide structures by selective silicon dioxide chemical-vapor deposition - Whittaker, Jed D. (2003)
A self-aligned thin-ﬁlm deposition technique was developed to mechanically attach carbon nanotubes to surfaces for the fabrication of structurally robust nanotube-based nanomechanical devices. Single-walled carbon nanotubes were grown by thermal chemical-vapor deposition (CVD) across 150-nm-wide SiO2 trenches. The nanotubes were mechanically attached to the trench tops by selective silicon tetraacetate-based SiO2 CVD. No ﬁlm was deposited on the nanotubes where they were suspended across the trenches.